OP0006 Influence of autonomic nervous system dysfunction in the genesis of sleep disorders in fibromyalgia patients. (15th June 2017) - Rizzi, M; Radovanovic, D; Santus, P; Airoldi, A; Frassanito, F; Vanni, S; Cristiano, A; Casale, R; Furlan, R; Atzeni, F; Sarzi-Puttini, P
Abstract : Background: Fibromyalgia (FM) is characterised by chronic musculoskeletal pain, autonomic nervous system (ANS) dysfunction, and disturbed sleep. Objectives: The aim of this study was to evaluate the influence of ANS dysfunction on the genesis of sleep disorders. Methods: Fifty consecutive Caucasian women (age 51.2±7.3 years) whose FM had been diagnosed on the basis of the 2010 ACR classification criteria were compared with 45 healthy female controls matched for age and body mass index.All of the FM patients underwent a clinical, polysomnographic and autonomic profile evaluation at rest and during a tilt test to determine muscle sympathetic nerve activity (MSNA), plasma catecholamine levels, and the spectral indices of cardiac sympathetic (LFRR ) and vagal (HFRR ) modulation computed by means of the spectrum analysis of RR during sleep. Results: The FM patients had more tender points (p<0.001), a higher ESS score (p<0.001), and more signs and symptoms of orthostatic intolerance (p<0.001) than the controls. They also had a higher heart rate (HR), more MSNA and a higher LF/HF ratio, and lower HFRR values at rest. The increase in tilting-induced MSNA was less in the FM patients (2±1 vs 16±3.1 bursts/min, p<0.05; 2±1 vs 12±2.8 bursts/100 p<0.05), whereas the trend in the spectral indices of the cardiac autonomic profile (LFRR and the LF/HF ratio) and plasma catecholamine levels were similar in the two groups; furthermore, the decrease in the index of cardiac vagal modulation (HFRR ) was also less in the patients (HFRR NU -17.3±3.2 vs -32.4±4.8, p<0.05; HFRR ms 2 -148±50 vs -857±374, p<0.05). The stepwise tilt induced syncope or pre-syncope in 23 of the 50 patients (46%) and two of the 45 controls (5%) (p<0.001), Their sleep was less efficient (p<0.01), and they had a higher proportion of stage 1 non-REM sleep (p<0.001), experienced many arousals and periodic limb movements (PLMs) per hour of sleep (p<0.001) and a high proportion of periodic breathing (PB%) (p<0.0001). Their cyclic alternating pattern (CAP) rate was significantly increased (p<0.001).During sleep, the patients had a higher HR, and LF/HF ratio, and lower HFRR, differences that were more marked during non-REM sleep, as were the presence of CAP, PB and PLMs. PLMs were mainly observed during CAP subtype A2 and A3. As in the tilt test, there was also a decrease in the index of cardiac vagal modulation during sleep: the decrease in HRRR during sleep and in comparison when awake was less in the FMS patients than the controls (11.6±4.2 vs 31.1±5.3 NUs, p<0.01; 45±38 vs 403±281 ms 2, p<0.0001) The number of tender points, pain VAS, the CAP rate, the PB% of sleeping time and the PLMI all seemed to correlate positively with HR and the LF/HF ratio, and negatively with HFRR during sleep Conclusions: Our data confirm that the FM patients have an autonomic nervous system dysfunction that is consistent with sympathetic over-activity due to the intensity of chronic pain when awake and during sleep. These findings explain the excessive rate of syncope observed in the FM population during wakefulness, and the increased presence of CAP, PB and PLMs during sleep. Disclosure of Interest: None declared